2016
DOI: 10.1007/s10552-016-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling how substitution of sedentary behavior with standing or physical activity is associated with health-related quality of life in colorectal cancer survivors

Abstract: PurposePrevious research indicates that sedentary behavior is unfavorably associated with health-related quality of life (HRQoL) of colorectal cancer (CRC) survivors. Using isotemporal substitution modeling, we studied how substituting sedentary behavior with standing or physical activity was associated with HRQoL in CRC survivors, 2–10 years post-diagnosis.MethodsA cross-sectional study was conducted in stage I–III CRC survivors (n = 145) diagnosed at Maastricht University Medical Center+, the Netherlands (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 46 publications
(48 reference statements)
3
79
0
Order By: Relevance
“…32,36 Fatigue Two prospective studies on sedentary behavior and fatigue, both conducted in breast cancer survivors, produced contrasting outcomes. Five studies showed no association, 32,34,42,44,46 three publications identified statistically significant, positive associations, 30,47,48 and 1 study identified significant positive associations when MVPA was included in the model, but not when light physical activity was included. 37 Results from cross-sectional studies were also mixed.…”
Section: Quality Of Lifementioning
confidence: 94%
See 3 more Smart Citations
“…32,36 Fatigue Two prospective studies on sedentary behavior and fatigue, both conducted in breast cancer survivors, produced contrasting outcomes. Five studies showed no association, 32,34,42,44,46 three publications identified statistically significant, positive associations, 30,47,48 and 1 study identified significant positive associations when MVPA was included in the model, but not when light physical activity was included. 37 Results from cross-sectional studies were also mixed.…”
Section: Quality Of Lifementioning
confidence: 94%
“…41 Regression coefficients ranged from 0.03 (95% CI, −0.05, 0.12) to 8.4 (95% CI, 0.05, 16.3). 37 A single cross-sectional study identified a statistical association at the 50th percentile of sedentary time, 43 but 6 cross-sectional studies (7 publications) in prostate, 32 colon/colorectal, 45,47,48 and breast cancer survivors 39,41 did not identify any significant associations. One prospective study did identify a statistically significant, positive association between sedentary time and depression (F = 4.97; P = .03), 40 whereas another did not (P for trend = .54).…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study of 145 colorectal cancer survivors also found that greater sedentary time was associated with lower physical functioning, higher fatigue scores, and lower quality of life and lower role functioning [12,13]. Similarly, in 98 prostate cancer survivors, there was a trend toward an association between sedentary lifestyle and poorer quality of life [14].…”
Section: Physical Activitymentioning
confidence: 99%